2021
DOI: 10.3390/jcm10173947
|View full text |Cite
|
Sign up to set email alerts
|

Classification and Assessment of Medication Risk in the Elderly (CARE): Use of a Medication Risk Score to Inform Patients’ Readmission Likelihood after Hospital Discharge

Abstract: Existing risk tools that identify patients at high risk of medication-related iatrogenesis are not sufficient to holistically evaluate a patient’s entire medication regimen. This study used a novel medication risk score (MRS) which holistically evaluates medication regimens and provides actionable solutions. The main purpose of this study was to quantify adults ≥ 65 years with a high medication risk burden using the MRS and secondarily, appraise MRS association with hospital readmission. This retrospective coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
(23 reference statements)
1
1
0
Order By: Relevance
“…To reach statistical significance, our study should have needed 323 subjects. They are also consistent with another study that demonstrated an association between reduced MRS values and hospitalizations [14].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To reach statistical significance, our study should have needed 323 subjects. They are also consistent with another study that demonstrated an association between reduced MRS values and hospitalizations [14].…”
Section: Discussionsupporting
confidence: 92%
“…To date, others have validated that an elevated MRS is associated with several negative outcomes, which include ADEs, emergency department visits, hospitalizations, medical expenditures, and mortality [12,13]. Regarding readmission, San Filippo et al found that the MRS can preemptively identify patients at the highest risk of hospital readmission within 30 days post discharge [14]. Nevertheless, it is unknown whether the MRS can help pharmacists identify relevant MRPs during the transition from hospital to home, which could help reduce readmissions.…”
Section: Introductionmentioning
confidence: 99%
“…20 Patients with an MRS score of 20 or higher exhibited a 1.8-fold increased risk of 30-day readmission when discharged home. 20 The increased risk of readmission was only seen in patients discharged to home, as opposed to a skilled nursing facility or long-term care facility. 20 Among the 1386 patients included in this study, 98 (7.1%) were discharged home with a high-risk score over 6 months.…”
Section: Conclusion: This Study Demonstrates That the Mrs-cdss Effect...mentioning
confidence: 94%
“…20 Among the 1386 patients included in this study, 98 (7.1%) were discharged home with a high-risk score over 6 months. 20 These data highlight the potential of the MRS as a tool to identify a manageable subset of high-risk hospital inpatients at an elevated risk of 30-day readmission, thereby enabling targeted efforts during TOC. This cross-sectional analysis aims to quantitatively assess and describe the interventions identified by pharmacists using the MRS-CDSS.…”
Section: Conclusion: This Study Demonstrates That the Mrs-cdss Effect...mentioning
confidence: 99%
See 1 more Smart Citation